Managing purchasing : organizing, planning and control - Farrington, Brian; Waters, Derek W. F. (London : Chapman and Hall, 1994)
This book is about: People and money; Materials; Financial reporting, the purchasing forecast and the corporate purchasing plan; The recruitment process; ...
Keywords: Management; Industrial procurement -- Management; Materials management